2022
DOI: 10.1007/s00406-022-01542-1
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine once- versus multiple-daily dosing: a two-center cross-sectional study, systematic review and meta-analysis

Abstract: Evidence regarding effectiveness and safety of clozapine once- vs. multiple-daily dosing is limited. We compared demographic and clinical parameters between patients with once- vs. multiple-daily dosing in the Department of Psychiatry and Psychotherapy, University of Regensburg, Germany (AGATE dataset), and the Department of Psychiatry, Lausanne University Hospital, Switzerland, using non-parametric tests. Effectiveness and safety outcomes were available in the AGATE dataset. We performed a systematic review i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…These factors may be associated with the dosing regimen of clozapine. Kuzo et al 9 found that divided dosing led to more severe clinical symptoms and a higher clozapine dose than once-daily dosing. Also, based on the chart review, some data may be incomplete, such as adverse effects and reasons for clozapine discontinuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may be associated with the dosing regimen of clozapine. Kuzo et al 9 found that divided dosing led to more severe clinical symptoms and a higher clozapine dose than once-daily dosing. Also, based on the chart review, some data may be incomplete, such as adverse effects and reasons for clozapine discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, dosing regimens of clozapine differ between countries. In a 2-center cross-sectional study in Germany and Switzerland, Kuzo et al 9 found that once-daily dosing of clozapine was prescribed in 25.2% to 32.3% of cases, whereas in a study in the United States and Canada, Takeuchi et al 10 found that once-daily dosing of clozapine was commonly prescribed in approximately 75% of cases. In addition, a cross-sectional study comparing the actual plasma concentration of clozapine achieved by once-daily and divided dosing regimens in patients with schizophrenia or schizoaffective disorders found no difference in psychotic symptom resolution, adverse effects, or peak/trough plasma concentration between once-daily and divided dosing regimens.…”
Section: Introductionmentioning
confidence: 99%
“… 190 , 234 , 378 Importantly, recent findings indicate that clozapine administration partly during daytime may not reduce the burden of sedation. 379 Emphasizing nocturnal administration whenever possible while taking into account individual preferences appears to be more promising also given that complex dosing instructions might be too demanding for some patients. 379 Adding aripiprazole constitutes another option.…”
Section: Side Effects Of Clozapinementioning
confidence: 99%
“… 379 Emphasizing nocturnal administration whenever possible while taking into account individual preferences appears to be more promising also given that complex dosing instructions might be too demanding for some patients. 379 Adding aripiprazole constitutes another option. 88 , 378 Augmentation with modafinil has also been discussed, but findings from a placebo-controlled pilot trial were not generally supportive.…”
Section: Side Effects Of Clozapinementioning
confidence: 99%
“…Investigators recently conducted a comparative study of patients from two psychiatric hospitals in two European hospital networks who were treated with one of the two clozapine dosing regimens. They also performed a systematic review and meta‐analysis of studies, with the aim of addressing potential differences in safety and effectiveness between the dosing regimens (Kuzo et al 2022).…”
mentioning
confidence: 99%